Airway and Respiration Parameters Improve Following Vocal Fold Medialization: A Prospective Study. (December 2015) - Asik, M. Burak; Karasimav, Ozlem; Birkent, Hakan; Merati, Albert L.; Gerek, Mustafa; Yildiz, Yavuz
Objectives/Hypothesis: Laryngeal medialization procedures such as injection laryngoplasty (IL) and thyroplasty type 1 (TT1) are standard techniques for the treatment of glottic insufficiency related to unilateral vocal fold paralysis (UVFP). These procedures reliably improve the voice and may also improve swallowing function. Despite the association of laryngeal paralysis with airway regulation, there is little published on the effect of UVFP and its surgical treatment on respiration. The aim of this prospective study was to evaluate the aerodynamic outcomes of UVFP patients before and after vocal fold medialization, either by IL or TT1. Methods: Consecutive patients with dysphonia due to UVFP were included in this prospective study between 2012 and 2014. Nineteen patients were investigated (5 females, 14 males) with a mean age of 37.05 ± 17.8 years. Eight patients were treated by IL while 11 patients received TT1. The patients were subjected to Modified Medical Research Council (MMRC) and Borg dyspnea scales, maximum phonation time (MPT) measurement, spirometry, and cycle ergometry, pre- and postoperatively at 2 months. Results: There was a statistically significant increase in MPT from 5.5 ± 3 seconds to 11.2 ± 4.9 seconds postoperatively ( P < .001). The MMRC and Borg dyspnea scales also showed significant improvement postoperatively ( P < .001, P = .006, respectively). The change in spirometric parameters (peak expiratory flow, forced expiratory volume in 1 second, forced vital capacity, and peak inspiratory flow) were nonsignificant, while there was a significant improvement in cycle ergometry test postoperatively ( P = .018). Conclusion: Laryngeal medialization procedures such as IL and TT1 improve UVFP patients' respiration-related quality of life and aerodynamic performance with no significant changes in spirometry.